Metacognition, rumination and suicidal ideation: An experience sampling test of the self-regulatory executive function model. (September 2021) - Hallard, Robert I.; Wells, Adrian; Aadahl, Vikki; Emsley, Richard; Pratt, Daniel
Highlights: Metacognitive beliefs about the need to control thoughts predicted self-punishment. Worry- and punishment-related thought control strategies predicted suicide ideation. Distraction, social control and reappraisal negatively predicted suicidal ideation. Abstract: A relationship between rumination and suicidal ideation is well-evidenced. A role for thought suppression has also been suggested but under-explored. The present study assessed the relative contribution of rumination and a range of thought control strategies in the understanding of suicidal ideation, within the theoretical framework of the self-regulatory executive function (S-REF) model (Wells & Matthews, 2015). Twenty-four participants who had experienced suicidal ideation in the last two months completed trait-level measures of metacognitive beliefs and momentary sampling measures of thought control strategy use, rumination and suicidal ideation over six days. Maladaptive thought control strategy use (worry and punishment), alongside rumination, predicted suicidal ideation. Adaptive strategies (distraction, social control and reappraisal) emerged as negative predictors. Metacognitive beliefs about the need to control thoughts predicted the use of punishment- but not worry-based thought control strategies. Thought control strategy use is as important in the development of suicidal ideation as rumination. The S-REF model represents a promising new approach to understanding these processes in the development of suicidal ideation.